Tuning composition and architecture of biomimetic scaffolds for enhanced matrix synthesis by murine cardiomyocytes. Issue 2 (19th May 2014) - Gishto, Arsela; Farrell, Kurt; Kothapalli, Chandrasekhar R.
Abstract A major onset of heart failure is myocardial infarction, which causes the myocardium to lose cardiomyocytes and transform into a scar tissue. Since mammalian infarcted cardiac tissue has a limited ability to regenerate, alternative strategies including implantation of tissue‐engineered scaffolds at the site of damaged myocardium have been explored. The goal is to enable in situ cardiac reconstruction at the injured myocardium site, replace the lost cardiomyocytes, deliver the required biomolecules, and remodel the extracellular matrix (ECM). ECM synthesis and deposition by cardiomyocytes within such scaffolds remains categorically unexplored. Here, we investigated the survival, ECM synthesis and deposition, and matrix metalloproteinases (MMPs) release by cardiomyocytes within three‐dimensional (3D) substrates. Rat cardiomyocytes were cultured for three weeks within two structurally different substrates: 3D collagen hydrogels or polycaprolactone (PCL) nanofibrous scaffolds. The concentration and composition of the hydrogels was varied, while PCL nanofibers were surface‐modified with various ECM proteins. Results showed that myocyte attachment and survival was higher within collagen hydrogels, while myocyte alignment and beating was noted only within PCL scaffolds. Total protein synthesis by myocytes within PCL scaffolds was significantly higher compared to that within collagen hydrogels, although more protein was deposited as matrix within hydrogels. Significant ECM synthesis and matrix deposition, TIMP‐1, and MMP release were noted within modified collagen hydrogels and PCL nanofiber scaffolds. These results were qualitatively confirmed by imaging techniques. Results attest to the prominent role of scaffold composition and architecture in influencing cardiomyocyte phenotype, matrix synthesis and cytokines release, with significant applications in cardiac tissue remodeling strategies. © 2014 Wiley Periodicals, Inc. J Biomed Mater Res Part A: 103A: 693–708, 2015.